Medicare/Medicaid Insurance Status Is Associated With Reduced Lower Bilateral Knee Arthroplasty Utilization and Higher Complication Rates. (26th April 2022) - Mehta, Bella; Ho, Kaylee; Bido, Jennifer; Memtsoudis, Stavros G.; Parks, Michael L.; Russell, Linda; Goodman, Susan M.; Ibrahim, Said
Abstract : Whether to undergo bilateral total knee arthroplasty (BTKA) depends on patient and surgeon preferences. We used the National Inpatient Sample to compare temporal trends in BTKA utilization and in-hospital complication rates among TKA patients ≥50 with Medicare/Medicaid versus private insurance from 2007 to 2016. We used multivariable logistic regression to assess the association between insurance type and trends in utilization and complication rates adjusting for individual-, hospital-, and community-level covariates, using unilateral TKA (UTKA) for reference. Discharge weights were used for nationwide estimates. About 132, 400 (49.5%) Medicare/Medicaid patients and 135, 046 (50.5%) privately insured patients underwent BTKA. Among UTKA patients, 62.7% had Medicare/Medicaid, and 37.3% had private insurance. Over the study period, BTKA utilization rate decreased from 7.18% to 5.63% among privately insured patients and from 4.59% to 3.13% among Medicaid/Medicare patients ( P trend difference <0.0001). In multivariable analysis, Medicare/Medicaid patients were less likely to receive BTKA than privately insured patients. Although Medicare/Medicaid patients were more likely to develop in-hospital complications after UTKA (adjusted odds ratio, 1.06; 95% confidence interval, 1.002 to 1.12; P = 0.04), this relationship was not statistically significant for BTKAs. In this nationwide sample of TKA patients, BTKA utilization rate was higher in privately insured patients compared with Medicare/Medicaid patients. Furthermore, privately insured patients had lower in-hospital complication rates than Medicare/Medicaid patients.